2014
DOI: 10.1037/xap0000025
|View full text |Cite
|
Sign up to set email alerts
|

The influence of causal connections between symptoms on the diagnosis of mental disorders: Evidence from online and offline measures.

Abstract: An experiment conducted with students and experienced clinicians demonstrated very fast and online causal reasoning in the diagnosis of Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) mental disorders. The experiment also demonstrated that clinicians' causal reasoning is triggered by information that is directly related to the causal structure that explains the symptoms, such as their temporal sequence. The use of causal theories was measured through explicit, verbal diagnostic j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…This effect suggests (a) that participants' causal beliefs affect online, fast, and efficient Type 1 processes during reading and (b) that these Type 1 processes involve the computation of causal coherence. Our findings complete previous findings by Flores, Cobos, López, Godoy, and González-Martín (2014). This study showed that RTs and diagnostic judgments are affected by the temporal coherence between the observed sequence of symptoms and the temporal sequence implicated by causal assumptions of the participating clinicians.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This effect suggests (a) that participants' causal beliefs affect online, fast, and efficient Type 1 processes during reading and (b) that these Type 1 processes involve the computation of causal coherence. Our findings complete previous findings by Flores, Cobos, López, Godoy, and González-Martín (2014). This study showed that RTs and diagnostic judgments are affected by the temporal coherence between the observed sequence of symptoms and the temporal sequence implicated by causal assumptions of the participating clinicians.…”
Section: Discussionsupporting
confidence: 90%
“…One may think that more experienced clinicians would be less affected by causal considerations in diagnostic decision making as they receive extensive training on the correct use of the DSM. The experimental findings cited earlier prove otherwise Flores, Cobos, López, Godoy, & González-Martín, 2014;Kim & Ahn, 2002). Conversely, it might be argued that experienced clinicians are especially vulnerable to influences of causal knowledge because Type 1 processes play an important role in experts' reasoning.…”
Section: Type 1 Causal Reasoning Processes In Diagnostic Decision Makmentioning
confidence: 90%
See 1 more Smart Citation
“…The factor that ranked highest among all choices was also the most central factor in the PCR network: depressed mood. This is in line with literature demonstrating that clinicians causal reasoning when dealing with diagnostic information concerning mental disorders is related to the causal model they adhere to [33][34][35].…”
Section: Relation To the Literaturesupporting
confidence: 89%
“…Previous studies also indicated that clinicians’ causal assumptions are related to treatment preferences (e.g., Ahn et al, 2009 ; Flores, Cobos, López, Godoy, & Ganzález-Martín, 2014 ), but no study investigated how personal theories of disorders are linked to inferences about the relative effectiveness of treatments. De Kwaadsteniet, Hagmayer, Krol, and Witteman (2010) studied clinicians’ causal models of individual clients (i.e., their clinical case conceptions) and found that these models predicted clinicians’ judgments of the relative effectiveness of different interventions for the specific client.…”
mentioning
confidence: 99%